A household solid waste recycling programme in Stellenbosch : householders' attitudes and willingness to participate - Makau, Mafalla E. (Mafalla Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2006.